The glocalization of parkour: a New Zealand/Aotearoa case study - Puddle, D.; Wheaton, B.; Thorpe, H. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
Globalization has led to the increased sportization of parkour, one of the world`s newest lifestyle sports. This paper investigates the parkour scene in New Zealand, where attempts to develop and support parkour have resulted in the formation of a national governing body (NGB). Parkour NZ, formed in 2011 by local practitioners and the first NGB for parkour to be registered as a charity, is undergoing increased sportization in both traditional and unique ways. We examine the motivations that inspired its formation, registration as a charity and some of the ways it has negotiated the sportization process while accounting for New Zealand parkour community values. Our case study adds to understandings of glocalization and sportization of informal lifestyle sports, and highlights how parkour practitioner values are negotiated within new organizational spaces.